Effects of engineered silver nanoparticles on the growth and activity of ecologically important microbes. Issue 5 (17th February 2014) - Beddow, Jessica; Stolpe, Björn; Cole, Paula; Lead, Jamie R.; Sapp, Melanie; Lyons, Brett P.; Colbeck, Ian; Whitby, Corinne
Summary Currently, little is known about the impact of silver nanoparticles (AgNPs) on ecologically important microorganisms such as ammonia‐oxidizing bacteria (AOB). We performed a multi‐analytical approach to demonstrate the effects of uncapped nanosilver (uAgNP), capped nanosilver (cAgNP) and Ag2SO4 on the activities of the AOB: Nitrosomonas europaea, Nitrosospira multiformis and Nitrosococcus oceani, and the growth of Escherichia coli and Bacillus subtilis as model bacterial systems in relation to AgNP type and concentration. All Ag treatments caused significant inhibition to the nitrification potential rates (NPRs) of Nitrosomonas europaea (decreased from 34 to < 16.7 μM NH4+ oxidized day−1), Nitrosospira multiformis (decreased from 46 to < 24.8 μM NH4+ oxidized day−1) and Nitrosococcus oceani (decreased from 26 to < 18.4 μM NH4+ oxidized day−1). Escherichia coli‐Ag interactions revealed that the percentage of damaged E. coli cells was 45% greater with Ag2SO4, 39% with cAgNPs and 33% with uAgNPs compared with controls. Generally, the inhibitory effect on AOB NPRs and E. coli/B. subtilis growth was in the following order Ag2SO4 > cAgNP > uAgNP. In conclusion, AgNPs (especially cAgNPs) and Ag2SO4 adversely affected AOB activities and thus have the potential to severely impact key microbially driven processes such as nitrification in the environment.